Long-term effect of Donald Trump’s usage of white supremacist rhetoric on public discourse: a content analysis of comments to a tweet about Donald Trump’s dinner with Nick Fuentes on Twitter - Simmons, Ethan (My University, 2023)
This qualitative study performed a content analysis of the top 50 comments on a tweet about Donald Trump and his dinner with white supremacist Nick Fuentes. This study aimed to see if any long-lasting effects were caused by Trump's utilization of white supremacist dogmatic rhetoric. The comments were coded for relationships with each other and prevalent themes; five were apparent 1) Criticism of the media, 2) Mention of Trump's base, 3) Use of the term white supremacist, 4) Use of term antisemitism, 5) and Criticism of Trump or Republican Party. The most pervasive themes explored were the sentiment that Trump is associated with white supremacy, a notion that tarnished him and his base, according to the findings of this analysis.
Keywords: white supremacy; dogmatic rhetoric; social media; Donald Trump